2016
DOI: 10.1007/s00216-016-9797-0
|View full text |Cite
|
Sign up to set email alerts
|

The development of plasma pseudotargeted GC-MS metabolic profiling and its application in bladder cancer

Abstract: Bladder cancer (BC) is a fatal malignancy with considerable mortality. BC urinary metabolomics has been extensively investigated for biomarker discovery, but few BC blood metabolomic studies have been performed. Hence, a plasma pseudotargeted metabolomic method based on gas chromatography-mass spectrometry with selected ion monitoring (GC-MS-SIM) was developed to study metabolic alterations in BC. The analytical performance of the developed method was compared with that of a nontargeted method. The relative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…In total, 252 metabolites from cell samples and 290 metabolites from tissue samples were determined for pseudo‐targeted data collection and quantification. The system parameter settings and metabolite identification were similar to those in a previous report 20…”
Section: Methodsmentioning
confidence: 94%
“…In total, 252 metabolites from cell samples and 290 metabolites from tissue samples were determined for pseudo‐targeted data collection and quantification. The system parameter settings and metabolite identification were similar to those in a previous report 20…”
Section: Methodsmentioning
confidence: 94%
“…Additionally, a 3-fold volume QC sample and a hydrocarbon mixture were analyzed to annotate the low-abundance metabolites and to calculate the retention index (RI) based on n-alkanes, respectively. The identification of urinary metabolites was similar to a previous report [8]. In short, metabolites were annotated based on commercial mass spectral libraries (Mainlib, NIST, Wiley, and Fiehn) and a homemade metabolite library and were further verified using the standards’ RT/RI.…”
Section: Methodsmentioning
confidence: 69%
“…This method has also been used to study BC [7, 8], especially to identify biomarkers [911]. Huang et al [9] found that a combined urinary biomarker composed of carnitine C9:1 and an unknown metabolite had high sensitivity and specificity in discriminating 27 BC patients from 32 healthy controls (HCs), although no validation was performed.…”
Section: Introductionmentioning
confidence: 99%
“…A QP 2010 GC-MS system (Shimadzu, Japan) with a DB-5 MS fused-silica capillary column (30 m × 0.25 mm × 0.25 μm, Agilent Technologies, Santa Clara, CA, USA) was used for metabolic profiling. A pseudotargeted GC-MS metabolomics method was established elsewhere ( 14 16 ). The ion peak area of the metabolite was normalized to the internal standard and multiplied by 1 × 10 6 , then utilized for following data processing.…”
Section: Methodsmentioning
confidence: 99%